Pengaruh Stres Kerja dan Kompensasi Terhadap Keinginan Berpindah (Turnover Intention) Pada PT Tiki Jalur Nugraha Ekakurir (JNE) Hub. Sukaraja - Melinda Tiarasari; Arga Sutrisna; Suci Putri Lestari (CV. Ulil Albab Corp, 2023)
PT Tiki Jalan Nugraha Ekakurir Hub. Sukaraja mentioned the number of employees who moved and stopped working. The purpose of this study is to determine the description of Job Stress, Compensation and Turnover Intention, and also to determine the partial and simultaneous effect of job stress, compensation on Turnover Intention. The method used in this research uses quantitative methods through the causality method with a case study approach. Primary and secondary data sources with data collection techniques through interviews and questionnaires to employees of PT Tiki Jalan Nugraha Ekakurir Hub. Sukaraja. The results of this study are that at PT Tiki Jalan Nugraha Ekakurir Hub. Sukaraja regarding compensation work stress and employee turnover intention has quite high criteria, meaning that employees will leave if the compensation provided by the company is not guaranteed. Therefore work stress and compensation together have a significant effect on turnover intention. Meanwhile, partially compensation has no effect on turnover intention.